Gut microbiota-derived acetate promotes long-term recovery through angiogenesis guided by lymphatic ingrowth in older adults with stroke - Yuan, Yujia; Li, Linlin; Wang, Jingjing; Myagmar, Bat-Otgon; Gao, Yuxiao; Wang, Huan; Wang, Zhao; Zhang, Cong; Zhang, Xiangjian (Frontiers in Neuroscience, 2024)
IntroductionIschemic stroke is a leading cause of morbidity and mortality in older adults. Therefore, in this study, we sought to understand the interplay between the microbiota, gut, and brain in the context of stroke in older adults.ObjectiveTo determine whether gut microbiota from younger individuals promotes recovery through angiogenesis in both elderly stroke patients and aged stroke mice, we explored the changes in gut microbiota and the correlation between short-chain fatty acids (SCFAs) and angiogenesis in the aged stroke population. Then, we altered the gut microbiome in aged mice by transplanting microbiota from younger donors before inducing experimental stroke to explore the mechanism by which gut microbiota-derived SCFAs promote angiogenesis.MethodsPart I: We conducted a single-center, double-blind trial to compare gut microbiota diversity and SCFA levels in fecal samples from older stroke patients with those from younger stroke patients. Additionally, we measured levels of vascular endothelial growth factor (VEGF) and VEGFC levels in plasma to assess their correlation with SCFA levels. Part II: We performed fecal microbiota transplantation (FMT) 3 days before inducing ischemic stroke in aged male mice (16–18) via distal middle cerebral artery occlusion (dMCAO). The FMT was conducted using gut microbiomes from either young donors (2–3 months) or aged donors (16–18 months).ResultsIn older stroke patients, gut microbiota diversity was significantly reduced compared to that in younger stroke patients. Furthermore, levels of acetate, a bacterially derived SCFA, were lower and positively correlated with angiogenesis markers (VEGF and VEGF-C). In aged stroke mice, transplantation of young microbiota improved stroke outcomes by promoting angiogenesis, which was facilitated by lymphatic ingrowth into the cortex. This protective effect was linked to gut microbiota-derived acetate, which enhanced lymphangiogenesis by replenishing acetyl coenzyme A.Conclusions(a) Gut microbiota-derived acetate promotes angiogenesis post-stroke and (b) lymphatic ingrowth into the cerebral cortex was observed in post-dMCAO mice. These findings suggest that selectively promoting SCFA-producing bacteria, particularly acetate-producers, could be a promising therapeutic strategy to reduce functional impairments in older stroke subjects.